Immersion in water during labor and delivery - De Angelis, Carlo; De Angelis, Chiara; Santangelo, Fabrizia; Saccone, Gabriele; Ioffredo, Daniela; Cinzia Paino, Jessica Anna; Di Spiezio Sardo, Attilio (Perinatal Medicine Foundation, 2020)
Objective: Immersion in water during labor and delivery has been studied as an alternative form of obstetric care. The aim of this study was to evaluate obstetrics and neonatal outcomes of women intending to use immersion in water for labor and delivery. Methods: This was a retrospective observational study conducted at a single center in Italy from January 2004 to January 2016. The clinical records of pregnant women intending to use immersion in water for labor and delivery were collected in a dedicated database and included in the study. Only the women who underwent immersion in water starting from the first stage of labor were included in the study. Inclusion criteria were women with uncomplicated singleton gestations and cephalic presentation at or later than 37 weeks of gestation, and with spontaneous onset of labor. The primary outcome of the study was the percentage of women who had both labor and delivery in water. Results: 389 women met the inclusion criteria and were included in the study. 256 (66%) were nulliparous, and 133 (34%) were multiparous. Out of the 389 women intending to use immersion in water for labor and delivery, 278 (71.5%) had labor and delivery in the water, 31 (8.0%) labor in water and delivery on land, and 80 (20.5%) had the first stage of labor in water, and the second stage and delivery on land. The incidence of perineal lacerations was 61.4%. Conclusion: The vast majority of the women who set out to labor and delivery in water achieve their aim.